Advances in phase equilibrium engineering of supercritical reactors - Pereda, Selva (2009)
This review summarizes the advances made in the last decade in understanding the effect of phase conditions in the performance of supercritical reactors and in the control of process outputs. The study covers heterogeneous-catalyzed and non-catalytic supercritical reactions and shows the experimental and modeling tools that have been applied to address the problem of keeping reactants and products in a homogeneous phase. © 2008 Elsevier B.V. All rights reserved.